2011
DOI: 10.4995/wrs.2011.827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Colour and Reproductive Rhythm on Rabbit Doe Production

Abstract: AbstrAct:In this experiment the effects of the colour of light and reproductive rhythm on rabbit does' production was examined. The does (n=122) were first inseminated at the age of 16.5 wk and housed in 2 rooms. White coloured light was applied (W), in the first room, and blue lighting (B) was used in the second room. In both rooms, the does were randomly divided into 2 subgroups and inseminated using a theoretical reproductive rhythm (interval between parturitions) of 42 (42D) and 56 d (56D), respectively. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
7
1
2
Order By: Relevance
“…The KR (on average 70.1 %) was consequently 2.1 % lower. In the given analysis, the KR was also lower than that reported by Castellini et al (2010), Manal (2010), Gerencsér et al (2011), Coutelet (2015, and Theau-Clément et al (2016). Furthermore, the LS was relatively low compared with results from the literature concerning the breeding goals of modern hybrid rabbit strains (Coutelet, 2015;Maertens and Buys, 2015;Maertens and De Bie, 2017).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The KR (on average 70.1 %) was consequently 2.1 % lower. In the given analysis, the KR was also lower than that reported by Castellini et al (2010), Manal (2010), Gerencsér et al (2011), Coutelet (2015, and Theau-Clément et al (2016). Furthermore, the LS was relatively low compared with results from the literature concerning the breeding goals of modern hybrid rabbit strains (Coutelet, 2015;Maertens and Buys, 2015;Maertens and De Bie, 2017).…”
Section: Discussioncontrasting
confidence: 52%
“…Schüddemage (1999), Carluccio et al (2004) and Coutelet (2015) found respective pregnancy rates between 64 % and more than 80 % and an average LS of between 8.1 and 10.7 total kits born in different breeds. In practice, the KR is lower than the conception rate and varies widely between 29 % and 90 % (Dimitrova et al, 2009;Castellini et al, 2010;Manal, 2010;Gerencsér et al, 2011;Coutelet, 2015;Theau-Clément et al, 2016). It has been previously shown that housing and feeding are factors which influence reproductive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the 2 treatments were assessed separately. The effects of parity order on reproductive traits were shown by Gerencsér et al (2011). In this paper, the effect of feeding program is discussed.…”
Section: Methodsmentioning
confidence: 99%
“…The origin of this breed was described by Szendrő et al (1998). The design of the experiment was shown in the previous paper Gerencsér et al (2011). At 11 wk of age the female rabbits were randomly placed in 2 rooms.…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers observed that increasing daily lighting length before insemination can be an efficient biostimulation method to improve the receptivity (TheauClément et al, 2008) and kindling rate of the does (Theau-Clément et al, 1990;Mirabito et al, 1994;Gerencsér et al, 2010). The effect of different lighting colours was also studied (Gerencsér et al, 2011). Moreover, according to Seitz (1997) and Selzer (2000), the change in light and dark periods is a signal for the does to nurse their kits.…”
Section: Introductionmentioning
confidence: 99%